(untitled) (Historia, 2021)
With the centenary of the outbreak of the South African War in 1999 approaching (or was it the Anglo-Boer War, the Boer War, the English War, or the Second War of Independence?) interest in this war by way of publications becomes increasingly apparent. This book, compiled by Ronald Hackett and published by P. G. de Lotz of London, is by far one of the most attractive publications yet on the South African War